Procedural, pregnancy, and short‐term outcomes after fetal aortic valvuloplasty. Issue 3 (26th March 2020) - Patel, Neil D.; Nageotte, Stephen; Ing, Frank F.; Armstrong, Aimee K.; Chmait, Ramen; Detterich, Jon A.; Galindo, Alberto; Gardiner, Helena; Grinenco, Sofia; Herberg, Ulrike; Jaeggi, Edgar; Morris, Shaine A.; et al.
Abstract: Objectives: We aimed to evaluate the effect of technical aspects of fetal aortic valvuloplasty (FAV) on procedural risks and pregnancy outcomes. Background: FAV is performed in cases of severe mid‐gestation aortic stenosis with the goal of preventing hypoplastic left heart syndrome (HLHS). Methods: The International Fetal Cardiac Intervention Registry was queried for fetuses who underwent FAV from 2002 to 2018, excluding one high‐volume center. Results: The 108 fetuses had an attempted cardiac puncture (mean gestational age [GA] 26.1 ± 3.3 weeks). 83.3% of attempted interventions were technically successful (increased forward flow/new aortic insufficiency). The interventional cannula was larger than 19 g in 70.4%. More than one cardiac puncture was performed in 25.0%. Intraprocedural complications occurred in 48.1%, including bradycardia (34.1%), pericardial (22.2%) or pleural effusion (2.7%) requiring drainage, and balloon rupture (5.6%). Death within 48 hr occurred in 16.7% of fetuses. Of the 81 patients born alive, 59 were discharged home, 34 of whom had biventricular circulation. More than one cardiac puncture was associated with higher complication rates ( p  < .001). Larger cannula size was associated with higher pericardial effusion rates ( p = .044). On multivariate analysis, technical success (odds ratio [OR] = 10.9, 95% confidence interval [CI] = 2.2–53.5, p = .003) and later GA at intervention (OR = 1.5, 95% CI = 1.2–1.9, p = .002) were associated with increased odds of live birth. Conclusions: FAV is an often successful but high‐risk procedure. Multiple cardiac punctures are associated with increased complication and fetal mortality rates. Later GA at intervention and technical success were independently associated with increased odds of live birth. However, performing the procedure later in gestation may miss the window to prevent progression to HLHS.